1997
DOI: 10.1046/j.1365-2842.1997.00507.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of two methods for occlusal contact registration with the T-Scan system

Abstract: Various authors have studied the reproducibility of occlusal contact by means of the T-Scan computerized system and obtained contradictory results. In the present work the value of the T-Scan system as a method for exploring occlusion has been analysed. For this purpose, the same variable, i.e. the number of contacts, was recorded in 31 subjects using the two operation modes enabled by the T-Scan and the respective results were then compared. After an analysis of variance was performed to test the equality of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 6 publications
1
11
0
1
Order By: Relevance
“…Contact area has frequently been measured with T-Scan II equipment (Tekscan Inc., Boston, MA, USA),16,17 which is a reliable method for the analysis and evaluation of occlusal contact distribution in maximum intercuspation. This value is calculated by multiplying the number of tooth contacts recorded by the T-Scan sensor by the size of a single pixel (1.6 mm 2 ), thus reflecting occlusal conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Contact area has frequently been measured with T-Scan II equipment (Tekscan Inc., Boston, MA, USA),16,17 which is a reliable method for the analysis and evaluation of occlusal contact distribution in maximum intercuspation. This value is calculated by multiplying the number of tooth contacts recorded by the T-Scan sensor by the size of a single pixel (1.6 mm 2 ), thus reflecting occlusal conditions.…”
Section: Discussionmentioning
confidence: 99%
“…After occlusal adjustment, both sides of posterior areas of the dentures had revealed comparable occlusal force equilibration with an insignificant difference. (14) After occlusal modification in group (C) and group (U), there's a uniform dental contact, which results in improved denture stability, higher control of mastication, and enhanced efficiency as introduced in previous articles. (15) Authors reported that balanced occlusion improves the adaptation at early loading after fitting new conventional complete dentures (16) .…”
Section: Discussionmentioning
confidence: 97%
“…(5) In group (C), more intensive pressures of artificial teeth at the working side will compromise supporting tissues and will be a factor for intensive resorption of edentulous ridge influencing residual ridge resorption. (19) While in group (U), increased stability and its related balanced occlusion could be due to denture retention enhancement and stability using the denture suction appliances. It provided a viable option to improve denture retention when the patient was unable to use other treatment methods.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 Fig. 4 The mean location and SD of the OLC are shown in each occlusal supporting group, classified according to Eichner's index. The locations of the OLC are expressed relatively, as in Fig.…”
Section: Occlusal Load Centermentioning
confidence: 99%
“…Thus it was difficult to apply bite force measurement to the diagnosis and evaluation of prosthetic treatment of the whole dentition. Recently, some systems using thin, pressure-sensitive film, such as photocclusion [1,3], the T-scan system [4,9], and the dental prescale system [6,19], were developed to measure occlusal load on multiple points in the dentition. However, it was hard to compare bite force among individuals, because its levels are influenced by age [2], gender [18], and facial morphology [11].…”
Section: Introductionmentioning
confidence: 99%